Health-state utility values and their time to deterioration in informal caregivers of older patients with chronic diseases - Pozet, Astrid; Falcoz, Antoine; Roller, Cécile; Jai, Taha; Meurisse, Aurelia; Nerich, Virginie (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess health state utility values (HSUVs) in caregivers of older patients with chronic diseases receiving or not receiving social worker support.MethodsThis multicentric open-label randomized study assigned caregivers to receive either an informational booklet alone or one accompanied by social worker support. Caregivers completed EQ-5D-3L each semester for 24 months. We reported caregiver HSUVs at baseline and after 6, 12, 18, and 24 months using EQ-5D-3L utility index scores and exploring their time to deterioration (TTD).ResultsAmong 179 included caregivers, the percentage reporting some or extreme problems on five EQ-5D-3L dimensions remained almost stable over time with a median EQ-5D-3L utility index score of 0.89 [0.80–1.00] at baseline (n = 177), 0.80 [0.80–0.89] at M6 (n = 125), and 0.80 [0.73–0.91] at M24 (n = 81). Among the respondents, 62% (n = 109) experienced a deterioration in EQ-5D-3L utility index score, with a median TTD of 9.1 months [95%CI 6.2–14.9] in the control group (CG) and 9.5 months [6.3–14.4] in the supportive intervention group (SIG) (HR = 1.06 [0.73–1.54]), p-value = 0.76.ConclusionOur study provides a catalog of HSUVs across different caregiver profiles and at various follow-up time points, which can inform future economic evaluations.Clinical trial registrationClinicalTrials.gov, NCT02626377.